Factors Influencing Accounting Students’ Career Choice As Public Accountants - Purwandika, Lendy Dara; Putri, Intan Lifinda Ayuning (Reviu Akuntansi, Keuangan, dan Sistem Informasi, 2025)
This study aims to determine the effect of internship experiences, income, work environment, and labor market considerations on accounting students' career choice as public accountants. The population in this study was all active accounting students of Universitas Brawijaya. The samples include 126 respondents of accounting students of Universitas Brawijaya based on established criteria, selected through the purposive sampling technique. The results of the data analysis by multiple regression processed by IBM SPSS 25 software exhibit that work environment and labor market considerations positively affect student career choice as public accountants, whilst the internship experience and income have no effect on accounting student career choice as public accountants. The implications of this study are useful as considerations for accounting students in choosing their careers and considerations for universities and the government to improve the quality of education and teaching.